2014
DOI: 10.1007/s12011-014-9968-9
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Onion Extract on Cadmium-Induced Oxidative Stress, Histological Damage, and Apoptosis in Rat Heart

Abstract: To date, there is no available information on the protective effect of onion (Allium cepa) extract (AcE) on cadmium (Cd)-induced cardiotoxicity. The present study was performed to assess the possible antioxidant and anti-apoptotic roles of AcE in Cd-induced cardiotoxicity in rats. A Cd group was injected subcutaneously with CdCl2 dissolved in saline at a dose of 2 ml/kg/day for 30 days, resulting in a dosage of 1 mg/kg Cd. The rats in the AcE-treated group were given 1 ml of AcE via intragastric intubation for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 33 publications
4
14
0
Order By: Relevance
“…SOD is an antioxidant enzyme that catalyses the conversion of anion superoxide (O 2 • ) into oxygen (O 2 ) and H 2 O 2 and CAT completing detoxification process initiated by SOD. The lower activities of SOD and CAT found in diabetic rats is in agreement with the previous studies (Alpsoy et al, 2014;Jemai & Sayadi, 2015). This was probably due to the increment of antioxidant enzyme usage to compensate with the increased production of ROS.…”
Section: Effects Of Hpe On Oxidative Stress Status Of Thoracic Aortasupporting
confidence: 92%
“…SOD is an antioxidant enzyme that catalyses the conversion of anion superoxide (O 2 • ) into oxygen (O 2 ) and H 2 O 2 and CAT completing detoxification process initiated by SOD. The lower activities of SOD and CAT found in diabetic rats is in agreement with the previous studies (Alpsoy et al, 2014;Jemai & Sayadi, 2015). This was probably due to the increment of antioxidant enzyme usage to compensate with the increased production of ROS.…”
Section: Effects Of Hpe On Oxidative Stress Status Of Thoracic Aortasupporting
confidence: 92%
“…Important Cd sources affecting human life are cigarette smoke, refined nutrients, water pipes, coffee, tea, products released by burning coal, shellfishes, fertilizers used, dyes and batteries containing Cd, and flue gases released in industrial production stages [7]. Occupational and environmental Cd exposure cause serious damages in the tissues like the placenta, kidney, liver, testis, heart, brain, and lungs [8][9][10][11][12][13][14][15]. Several investigations confirmed its transport across the placenta and accumulation in fetuses [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…36,37 Extensive studies have indicated that Cd exposure induced oxidative stress, histological damage, and cardiomyocyte apoptosis in the cardiac tissue of rats. 25 Therefore, it could be concluded that Cd induces cardiotoxicity and cell death along with myocardial ber necrosis in the cardiac tissue. In addition, numerous studies revealed that the exposure to Cd increased the ROS production with oxidative stress resulting in tissue damage in rats.…”
Section: Discussionmentioning
confidence: 99%
“…41 Furthermore, Cd exposure induced signicant histological changes, which led to myobrillar loss, oedema, vacuolization of cytoplasm, vitreous degeneration, inltration of dense focal inammatory cells and irregularity of myobrils in the cardiac tissues of chicken. 25 In another study, the mode of Cd-induced programmed necrosis in human endothelial cells along with DNA damage has been determined. 42 The results of the present study are consistent with those previously reported, which have proved that some genes (JNK, TNFa, RIPK1 and MLKL) related to necroptosis pathway remarkably increased as observed in the Cd + group in our experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation